(untitled) (Damascus University Journal of arts and humanities sciences, 2025)
The waste problem is one of the most important environmental problems in urban areas, and its quantities are increasing with the increase in population and the development of the standard of living. Solid waste is one of the most important pollutants that people suffer from, and it is solid or semi-solid materials that are disposed of as waste of no value, and are collected in unstudied landfills that do not meet health conditions, especially in developing and low-income towns, and lead to the transfers of pollutants to all elements of the surrounding environment, especially soil, and from there to plants, water and humans. Heavy metals are present in the soil naturally at concentration not exceeding 1mg/kg, but when these metals are the result of human activities and untreated waste is collected, they accumulate in living tissues, and with the passage of time form complexes with organic and inorganic materials and lead to pollution of the ecosystem. The Safita landfill represents a model of soil pollution, and it is one of the random dumps that receive mixed waste that is not previously sorted. The phenomenon of pollution has been scientifically verified, by conducting spurs, measurements, and tests to determine the concentration of heavy elements in the soil, and proposing an alternative plan to stop this pollution.